Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T16:41:45+01:00
A)18 * 23 + (-17) * 23=414-391=23
b)21*(-4)-(-5)*21=-84-(-105)=-84+105=21
c)13*(-15)+(-15)*(-12)=-195+180=-15
d)16 : (-2) - 4 : (-2)=-8-(-2)=-8+2=-6
e)9:(-3)-(-15):(-3)=-3-5=-8
f)-18: (-3) + (-21):3=6+(-7)=-1

powinno być dobrze ;)
21 4 21
2010-01-24T16:46:23+01:00
A)18*23+(-17)*23=18*23-17*23=414-391=23
b)13*(-15)+(-15)*(-12)=13*(-15)-15*(-12)=-195+180=-15
c)9:(-3)-(-15):(-3)=9:(-3)+15:(-3)=-3-5=-8
d)21*(-4)-(-5)*21=21*(-4)+5*21=-84+105=21
e)16:(-2)-4:(-2)=-8+2=-6
f)-18:(-3)+(21):3=6+7=13
17 4 17
2010-01-24T16:47:03+01:00
A)18*23+(-17)*23=414-391=23
b)13*(-15)+(-15)*(-12)=-195+180=-15
c)9:(-3)-(-15):(-3)=-3-5=-8
d)21*(-4)-(-5)*21=-84+105=21
e)16:(-2)-4:(-2)=-8+2=-6
f)-18:(-3)+(21):3=6-7=-1
9 4 9